Analisis Pengaruh Ekspor, Foreign Direct Investment (FDI), Nilai Tukar, dan Inflasi Terhadap Cadangan Devisa di Negara Asean-6 Tahun 2011-2022 - H, Herliani; Sukarniati, Lestari (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to determine the influence of exports, Foreign Direct Investment (FDI), exchange rates, and inflation on foreign exchange reserves in six ASEAN countries from 2011 to 2022. This research combines cross section and time series data to provide a comprehensive view. comprehensive, the data used is secondary data obtained from Word Bank. The research results show that simultaneously the variables exports, Foreign Direct Investment (FDI), exchange rates and inflation have a significant effect on foreign exchange reserves in six ASEAN countries. Meanwhile, partially the export variable has a positive and significant effect on foreign exchange reserves, and inflation has a negative and significant effect on the ASEAN-6 foreign exchange reserve variable. Meanwhile, the FDI and exchange rate variables have no effect on foreign exchange reserves in the six ASEAN countries.